IMPLEMENTASI ALGORITMA KRIPTOGRAFI ONE TIME PAD (OTP) DENGAN DYNAMIC KEY LINEAR CONGRUENTIAL GENERATOR (LCG) - Clawdia, Jhessica; Khairina, Nurul; Harahap, Muhammad Khoiruddin (STMIK Budi Darma, 2017)
Algorithms have an important role in the era of digitalization, by understanding the concept of algorithms can keep information security protected from third parties. Securing a password can increase the security of the data so that the sender can be more comfortable when sending messages to others. This paper aims to make Keys on OTP dynamically generated using random number generator Linear Congruential Generator (LCG) Method. This discussion provides the benefit of an extension of insight that key modifications to OTP can be made and can be dynamically created. Based on the research done, with the random number generator method Linear congruential generator then the key becomes Unique. So there is no repetition of the same key. This depends on the range of random numbers.